Creative Production and Exchange of Ideas - Iryna Sikora (Journal of Economics and Behavioral Studies, 2019)
This paper explores the relationship between individual creative productivity and learning aboutideas of others. I report evidence from a two-stage real-effort lab experiment, in which subjects perform ideageneration tasks. In the first stage some subjects observe creative output of other players, while the othersnot. This design makes possible to assess whether learning ideas of others is an important input for ideageneration and quantify its importance. In the second stage, I make ideas costly and study the subjects’willingness to pay for them. I compare the costs of ideas to the expected monetary benefits from increasedcreative productivity and characterize investment behavior of the subjects. The results show that observingoutput of others boosts productivity in creative tasks, but only when it shows truly new, previously unknownby the subject items. When ideas of others become costly, I find that the subjects do not act in a profitmaximizing way. To minimize the costs they choose to see the ideas of less creative players, which usually donot contribute many original items. As a result, the participants get less than optimum benefits. This effect ismore pronounced for subjects of lower creative ability, more risk-averse or self-confident participants andfemales. In aggregate, such behavior does not lead to the highest possible level of creative production. Thesefindings make an argument for policies that encourage exchange of information at a workplace (e.g.teamwork, workshops) and at the same time show the need for oversight, central planning of collaborativeactivities or other actions that may help to creative professionals to invest efficiently, when access to ideas ofothers is costly.